Analisis Evaluasi Kinerja Direktorat Jenderal Bina Produksi Holtikultura: Dengan Pendekatan Balanced Scorecard - Harjadi Sarjono (The Winners, 2006)
The target of this article is to expected lapping over of format and result of analysis evaluate performance from Directorate Generaling To Construct Production Holtikultura. Evaluation of this performance is conducted by collectedly questioner thatalloted to all farmer in some area in Indonesia during year 2002.